A HISTÓRIA EM TEMPOS DE PÓS-MODERNIDADE: ALGUNS COMENTÁRIOS - e Silva, Maria Manuela Sousa (PHOÎNIX, 2020)
This article claims, under the form of some coments, to explore the ambiguities and the ambivalences, as well the challenges, that historians have to face in order to rethink the place and true role of History in our postmodern society. In fact, just after the 70s, we live under the sign of relativism or, as Sennett has pointed some years ago, under "the tyranny of the self" which affects the traditional faith in the reason and in the Enlightenment norms that, since Modern times, had governed social life. Can historians, in this disturbed times, resist the growing sceptical wave that seems to jeopardize the historical craft? Or is our knowledge definitely condemned to be a rhetorical one, just an historical imagination ?